Identification of plant attributes common to existing fibers used in textile industry - Meneses, Veronica Michaela V.; Lumawig, Maria Josephine T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
The fast fashion industry and the increasing demand for synthetic fibers, such as polyester, are known to generate potential environmental hazards. The need to address the issues related to wastage and non-sustainability of fast fashion gave rise to slow fashion. To help promote the concept of farm to table program in the textile industry, this study aimed to identify a set of plant attributes common to existing cellulosic fibers used for textile end products. The study specifically identified the most commonly used natural cellulosic fibers and categorized them as seed, leaf or stem fibers, described and classified plant sources based on similar plant structures, described their fiber properties, and identified possible textile end products. An extensive review of related literature and interviews with the Philippine Textile Research Institute (PTRI) provided the source of data to identify the most commonly used fibers and their properties and end uses. Seed fibers covered in this study included cotton and kapok. Leaf fibers included abaca and pina. Stem fibers included flax, ramie and hemp. The study showed that the possibility of a plant to produce textile fibers can be initially observed by looking at the plant structure. Thus, when finding new sources of fibers, certain plant structures should be considered. Seed fibers, although the fiber does not occur in the seed itself but rather an outgrowth of a single epidermal cell, come from plants with a dicotyledon seed. Leaf fibers come from plants which have a parallel veined monocotyledon leaf. Stem fibers come from plants which are classified as herbaceous dicot. While the plant structure may suggest the possibility of producing textile fibers, the specific end use and fiber quality, however, cannot be deduced instantly. Specific fiber properties, fiber blending and textile finishing should be taken into account. Further research on the abundance, fiber properties, and plant structure of other natural cellulosic fibers is recommended.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman
Keywords: Plant fibers -- Philippines; Fiber plants -- Philippines; Textile fabrics, Synthetic -- Philippines; Textile industry -- Philippines; Textile waste -- Philippines